PERAN KOMUNIKASI INTERPERSONAL FRONT OFFICE DALAM MENINGKATKAN PENGALAMAN TAMU DI ASIALINK HOTEL BY PRASANTHY BATAM - Wulanda, Olivia Diva; Andri Wibowo; Lubis, Arina Luthfini; Fatimah, Zahara (JURNAL MEKAR, 2024)
This study discusses the critical role of interpersonal communication carried out by the front office team in enhancing the guest experience at the Asialink Hotel in Batam. Through qualitative research methods, data were collected via interviews and direct observations of both front office staff and hotel guests. The findings reveal that effective and friendly communication from the front office not only strengthens relationships with guests but also significantly contributes to guest satisfaction and loyalty. These results underscore the essential nature of communication skills within the hospitality industry and highlight their impact on service quality. The study suggests that management should prioritize training programs focused on enhancing these skills to improve overall guest experience. Furthermore, the front office staff demonstrated high levels of empathy, showing keen sensitivity to guest needs and a proactive approach to addressing complaints. Their supportive and positive attitudes were evident as they responded to guest concerns with spontaneity and clarity, using polite language and maintaining friendliness while providing information. The staff's ability to offer relevant supporting information further enhances guest experience. Additionally, the study found that the front office staff exhibited fairness and equality in their service delivery, ensuring that all guests received consistent, high-quality service without discrimination. This comprehensive approach to communication highlights its vital role in the success of the hospitality industry.